The Whale Pump: Marine Mammals Enhance Primary Productivity in a Coastal Basin - Roman, Joe; McCarthy, James J. (PLOS ONE, 2010)
It is well known that microbes, zooplankton, and fish are important sources of recycled nitrogen in coastal waters, yet marine mammals have largely been ignored or dismissed in this cycle. Using field measurements and population data, we find that marine mammals can enhance primary productivity in their feeding areas by concentrating nitrogen near the surface through the release of flocculent fecal plumes. Whales and seals may be responsible for replenishing 2.3×104 metric tons of N per year in the Gulf of Maine's euphotic zone, more than the input of all rivers combined. This upward “whale pump” played a much larger role before commercial harvest, when marine mammal recycling of nitrogen was likely more than three times atmospheric N input. Even with reduced populations, marine mammals provide an important ecosystem service by sustaining productivity in regions where they occur in high densities.